Between regional community and global society: Europe in the shadow of Schmitt and Kojève. (June 2017) - Rech, Walter; Grzybowski, Janis
While celebrated for bringing peace and prosperity to the region, European integration has been recently challenged by various internal and external crises that call the progressivist narrative of ever closer—and larger—union into question. Torn between regional community and global society, particularism and cosmopolitanism, and politics and technocracy, the European Union appears beset by fundamental tensions. In search of a different theoretical perspective on "the crisis, " some commentators have drawn on Carl Schmitt's political theory to emphasize key issues concerning political decisions, identities, and boundaries in Europe. Yet, Schmitt comes with his own blind spots. For the purpose of a critical engagement with Schmitt's potential insights and their limits, this article contrasts his approach with that of his contemporary Alexandre Kojève, who envisioned the integration of world society through economy, law, technology, and administration, a perspective not unfamiliar to the original story of European integration. In reconsidering the dialectic between Schmitt's and Kojève's positions, this article goes beyond their apparent contradictions and discusses attempts by both authors to reconcile the opposition, from Kojève's move to Empires to Schmitt's theory of the union, thereby illuminating deep-seated dilemmas of contemporary European politics which fundamentally condition its trajectory between contestation and re-constitution.